Recommendations for design and analysis of earth structures using geosynthetic reinforcements : EBGEO - Johnson, Alan; Deutsche Gesellschaft für Geotechnik (Berlin : Ernst & Sohn : German Geotechnical Society, 2011)
'The design and execution of earth structures using geosynthetic reinforcements is based on DIN1054, 2005 edition, the European executive standard EN14475 (reinforced fill) and ZTV E-StB, 2009 edition, with the associated terms of delivery, and the Geosynthetics Fact Sheet. Continuing on from the first edition in 1997 these EBGEO recommendations employ the partial safety factor concept. In addition to analysis and verification fundamentals and the demands placed on construction materials (ground, geosynthetics) several sections deal with the various applications: embankments on soft soils, reinforced foundation pads, transport routes, retaining structures, landfill engineering (reinforcement of parallel surface stratified systems), reinforced earth structures over point or linear bearing elements, foundation systems using geotextile encased columns, overbridging sytems in areas prone to subsidence, dynamic actions on geosynthetic reinforced systems.'--p. 4 of cover.
'Translation of the 2nd German edition.'
Includes bibliographical references.
Keywords: Earth movements and building; Slopes (Soil mechanics).; Fills (Earthwork).; Foundations -- Design and construction -- Standards; Structural analysis (Engineering).; Geosynthetics; Reinforced soils; Soil stabilization